ANALISIS KESULITAN BELAJAR MATEMATIKA SISWA DITINJAU DARI KEMAMPUAN KONEKSI MATEMATIKA - Fitri Jannatul Laili; Ratih Puspasari (STKIP PGRI Tulungagung, 2019)
This study aims to discribe what are the difficulties of learning mathematics experienced which students in terms of mathematical connections ability class VIII MTs. darul Falah Bendiljati. This research is a descriptive qualitative research using test and interview method. Research subjects randomly selected as many as 30 students from two classes. The results showed that each student has difficulty learning mathematics in terms of mathematical connection capabilities are: (1) Less understanding of mathematical concepts that have been studied; (2) Not connecting mathematical concepts to be studied with previously known concepts; (3) Quicly forgot a mathematical concept he did not understand; (4) The habit of learning by understanding the concept, so when given a slightly different matter the students find it difficult; (5) Consider mathematics as a science that interconnects one and other concepts seperately; (6) Less aware of the benefits of consepts in mathematics to support and improve his ability in other fields of science; (7) Understanding conceptsÂ that are not applied directly to life, so the concept of mathematics is a concept in a mathematics only and not used or in connect with daily life.